A coupled model of the global cycles of carbonyl sulfide and CO2: A possible new window on the carbon cycle. Issue 2 (12th June 2013) - Berry, Joe; Wolf, Adam; Campbell, J. Elliott; Baker, Ian; Blake, Nicola; Blake, Don; Denning, A. Scott; Kawa, S. Randy; Montzka, Stephen A.; Seibt, Ulrike; Stimler, Keren; Yakir, Dan; et al.
Abstract: [1] Carbonyl sulfide (COS) is an atmospheric trace gas that participates in some key reactions of the carbon cycle and thus holds great promise for studies of carbon cycle processes. Global monitoring networks and atmospheric sampling programs provide concurrent data on COS and CO2 concentrations in the free troposphere and atmospheric boundary layer over vegetated areas. Here we present a modeling framework for interpreting these data and illustrate what COS measurements might tell us about carbon cycle processes. We implemented mechanistic and empirical descriptions of leaf and soil COS uptake into a global carbon cycle model (SiB 3) to obtain new estimates of the COS land flux. We then introduced these revised boundary conditions to an atmospheric transport model (Parameterized Chemical Transport Model) to simulate the variations in the concentration of COS and CO2 in the global atmosphere. To balance the threefold increase in the global vegetation sink relative to the previous baseline estimate, we propose a new ocean COS source. Using a simple inversion approach, we optimized the latitudinal distribution of this ocean source and found that it is concentrated in the tropics. The new model is capable of reproducing the seasonal variation in atmospheric concentration at most background atmospheric sites. The model also reproduces the observed large vertical gradients in COS between the boundary layer and free troposphere. Using a simulation experiment, we demonstrate that comparing drawdown of CO2 with COS could provide additional constraints on differential responses of photosynthesis and respiration to environmental forcing. The separation of these two distinct processes is essential to understand the carbon cycle components for improved prediction of future responses of the terrestrial biosphere to changing environmental conditions. Key Points: Carbonyl sulfide can help falsify carbon cycle models Carbonyl sulfide can aid separation of NPP into GPP and Resp The oceanic COS source is probably much larger than currently thought